Author Correction: Protein-peptide association kinetics beyond the seconds timescale from atomistic simulations - Fabian Paul (Nature Portfolio, 2018)
In the original version of this Article, the Acknowledgement section omitted financial support from the Deutsche Forschungsgemeinschaft grant SFB 958/A4. This error has now been corrected in both the PDF and HTML versions of the Article.